Macroeconomic variables and their relationship with the stock prices of six Pacific Rim countries : a cointegration approach. - Liu, Ve Kiong. (2008)
This paper will employ the Johansen (1991) model to examine the relationship between the stock indices of six Pacific Rim countries (U.S., Japan, Singapore, Hong Kong, Korea, Indonesia and Malaysia) and their respective macroeconomic variables. The results of the Johansen (1991) test for cointegration proves the existence of a cointegrating relationship between stock returns and their macroeconomic variables for all the countries in the study.